2017
DOI: 10.1007/s00701-017-3418-3
|View full text |Cite
|
Sign up to set email alerts
|

Decompressive craniectomy in traumatic brain injury: usage and clinical outcome in a single centre

Abstract: BackgroundTwo randomised controlled trials (RCTs) of decompressive craniectomy (DC) in traumatic brain injury (TBI) have shown poor outcome, but there are considerations of how these protocols relate to real practice. The aims of this study were to evaluate usage and outcome of DC and thiopental in a single centre.MethodThe study included all TBI patients treated at the neurointensive care unit, Akademiska sjukhuset, Uppsala, Sweden, between 2008 and 2014. Of 609 patients aged 16 years or older, 35 treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…Decompressive craniectomy [ 42 ] is used when Step 1B is insufficient to reduce ICP or when adverse effects of the thiopental treatment are observed. Bi-fronto-temporal craniectomies are done, sparing the bone ridge in the midline when there are no mass lesions.…”
Section: Methodsmentioning
confidence: 99%
“…Decompressive craniectomy [ 42 ] is used when Step 1B is insufficient to reduce ICP or when adverse effects of the thiopental treatment are observed. Bi-fronto-temporal craniectomies are done, sparing the bone ridge in the midline when there are no mass lesions.…”
Section: Methodsmentioning
confidence: 99%
“…All patients were treated in accordance with a standardized ICP-oriented treatment protocol to avoid secondary insults [8,9]. Treatment goals were ICP ≤ 20 mmHg, CPP ≥ 60 mmHg, systolic blood pressure > 100 mmHg, central venous pressure 0-5 mmHg, pO 2 > 12 kPa, blood glucose 5-10 mmol/L, electrolytes within normal ranges together with normovolemia and body temperature < 38 °C.…”
Section: Treatment Protocolmentioning
confidence: 99%
“…While many studies have shown the efficacy of DC in reducing ICP and improving mortality from severe TBI, others have questioned on its usefulness. [ 3 4 6 14 15 16 17 ] A meta-analysis was published by Zhang et al . in 2017, analyzing four RCTs, five retrospective studies, and one prospective study in the role of DC in TBI.…”
Section: Discussionmentioning
confidence: 99%